On the composition of Canto General, by Pablo Neruda (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
The article is mainly concerned with the composition of Canto general. Although the material prganization of the work suggests an objective linearity of time, the omnipresence of the time and space of the I encompasses a subjective sircularity. It is the I who seems tio determine the metaphorical composition of the work. Relying on the analysis of four key poetic works, Alturas de Macchu Pichu, Recabarren, Flores de Punitaqui, and El gran océano, this attempts to explain how the rite of passage from a lonesome I to a egalitarian I, turns out to be the center of gravity of the mythological configuration of the work and of the cosmogony of its writing.
Keywords: Neruda; Canto General; chilean poetry; composition